Inovasi Pemasaran Produk Bunga Telang Kering Kelompok Tani Setaria - Dianti, Fingki; Alya Najla Fadillah; Feria Noor Cahayati; Fitria Nuraini; Nita Dwi Cahyani; Mariyah (ANDIL Mulawarman Journal of Community Engagement, 2025)
The Setaria Farmer Group faces various obstacles in marketing dried telang flowers. The main obstacle faced is the lack of knowledge in digital marketing and branding. The method carried out in community service conducted in Sanga Sanga District, Kutai kartanegara Regency at the Setaria Farmers Group includes several activities, namely field observations, farmer group interviews, social media education. Activities are carried out by providing material and training to the Setaria Farmer Group regarding the utilization of platforms that can be used to sell and promote products such as: (1) Basic understanding of social media, (2) Ethics and safety in social media, (3) Optimization of social media. This activity shows that the approach taken through interviews, observations, and social media education is quite effective in helping setaria farmer groups to understand how to maximize the potential of their dried telang flower products. Overall, this activity succeeded in building awareness of the importance of innovation in product marketing. With the new skills acquired, the Setaria Farmers Group now has a greater opportunity to increase sales of their dried telang flower products online.